Co-targeting triple-negative breast cancer cells and endothelial cells by metronomic chemotherapy inhibits cell regrowth and migration via downregulation of the FAK/VEGFR2/VEGF axis and autophagy/apoptosis activation - Scagliotti, Arianna; Capizzi, Laura; Cazzaniga, Marina Elena; Ilari, Alice; De Giorgi, Marco; Cordani, Nicoletta; Gallazzi, Matteo; Bruno, Antonino; Pelosi, Giuseppe; Albini, Adriana; Lavitrano, Marialuisa; Grassilli, Emanuela; et al. (Frontiers in Oncology, 2022)
High-dose standard-of-care chemotherapy is the only option for triple-negative breast cancer (TNBC) patients, which eventually die due to metastatic tumors. Recently, metronomic chemotherapy (mCHT) showed advantages in treating TNBCs leading us to investigate the anti-metastatic and anti-angiogenic potential of metronomic 5-Fluorouracil plus Vinorelbine (5-FU+VNR) on endothelial cells (ECs) and TNBCs in comparison to standard treatment (STD). We found that 10-fold lower doses of 5-FU+VNR given mCHT vs. STD inhibits cell proliferation and survival of ECs and TNBC cells. Both schedules strongly affect ECs migration, but only mCHT impairs TNBC cell migration. The two treatments disrupt FAK/VEGFR/VEGF signaling in both ECs and TNBC cells. mCHT but not STD treatment induces apoptosis in ECs, whereas it switches the route of cell death from apoptosis (as induced by STD) to autophagy in TNBC cells. mCHT-treated TNBCs-derived conditioned medium also strongly affects ECs’ migration, modulates different angiogenesis-associated proteins, and hampers angiogenesis in matrix sponge in vivo. In conclusion, mCHT administration of 5-FU+VNR is more effective than STD schedule in controlling cell proliferation/survival and migration of both ECs and TNBC cells and has a strong anti-angiogenic effect. Our data suggest that the stabilization of tumor growth observed in TNBC patients treated with mCHT therapy schedule is likely due not only to direct cytotoxic effects but also to anti-metastatic and anti-angiogenic effects.